Carbon-Based Smart Materials - Charitidis, Constantinos A.; Dragatogiannis, Dimitrios A.; Koumoulos, Elias P. (De Gruyter, 2020)
Presents technologies and key concepts to produce suitable smart materials and intelligent structures for sensing, information and communication technology, biomedical applications (drug delivery, hyperthermia therapy), self-healing, flexible memories and construction technologies. Novel developments of environmental friendly, cost-effective and scalable production processes are discussed by experts in the field.